A bright hot-bent integrated rock plate basin and its manufacturing process

By using double-layer glaze technology on the ceramic body, the content and distribution of aluminum ions and sodium potassium ions are respectively regulated, the problems of aluminum ion crystallization and sodium potassium ions are solved, and the high gloss and good gloss of the glaze surface are achieved mechanical properties.

CN118724616BActive Publication Date: 2025-02-11GUANGDONG SANFI CERAMICS GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411092409.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-02-11
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

The high content of aluminum ions in ceramic glaze will lead to crystallization, while the small content of aluminum ions will affect the mechanical properties and chemical corrosion resistance of the glaze. At the same time, sodium and potassium ions are prone to diffuse into the ceramic matrix at high temperatures, resulting in ion exchange and Glaze gloss decreases.

Method used

Using a double-layer glaze method, first apply a layer of glaze with high aluminum ion content on the blank. After it is dried, apply a layer of glaze with high sodium potassium ion content to regulate aluminum through silica stone. Ion content, the content of sodium potassium ions is regulated by sodium silicate, and the aluminum ion glaze layer and sodium potassium ion glaze layer are formed respectively. The aluminum ion glaze layer is used to prevent the diffusion of sodium potassium ions, and the sodium potassium ion layer prevents the crystallization of aluminum ions.

Benefits of technology

Effectively control aluminum ion crystallization and limit excessive diffusion of sodium and potassium ions, improve the gloss and overall aesthetics of the glaze, while maintaining the mechanical properties and chemical corrosion resistance of the glaze.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of ceramic materials, specifically a bright hot-bent integrated rock slab basin and its manufacturing process. The present invention adopts a double-layer glazing method, firstly applying a layer of glaze with high aluminum ion content on the blank, and then applying a layer of glaze with high sodium and potassium ion content after it is dried, wherein the aluminum ion content in the glaze is regulated by adding sillimanite, and the sodium and potassium ion content is regulated by adding sodium silicate, and an aluminum ion glaze layer and a sodium and potassium ion glaze layer are obtained respectively, and the aluminum ion glaze layer is used to prevent the sodium and potassium ions from diffusing into the blank. In addition, the sodium and potassium ion layer can also effectively prevent the crystallization of aluminum ions, thereby developing a bright hot-bent integrated rock slab basin that can effectively control the crystallization of aluminum ions and limit the excessive diffusion of sodium and potassium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic materials, and specifically relates to a bright hot-bent integrated rock slab basin and a manufacturing process thereof. Background Art

[0002] In the field of modern ceramic and stone product manufacturing, such as the production of rock slab basins, the aesthetics and durability of the glaze are one of the characteristics that consumers pay great attention to. In particular, the gloss and structural integrity of bright hot-bent one-piece rock slab basins are crucial to the market competitiveness of the product. However, the problem of aluminum ion crystallization has always been a huge challenge affecting the gloss of hot-bent one-piece rock slab basins. In glazes, the presence of aluminum ions is necessary because they can enhance the mechanical strength and chemical resistance of the glaze layer. However, when the concentration of aluminum ions is too high, especially during high-temperature firing, aluminum ions are prone to form crystals and precipitate, which is the phenomenon of crystallization. These precipitated crystals will destroy the smoothness and uniformity of the glaze, thereby significantly reducing the gloss of the glaze. In addition, the different coordination states of aluminum ions (such as tetrahedron or octahedron) also have an important influence on the formation of crystals and the characteristics of the glaze.

[0003] One solution is to reduce the aluminum ion content in the glaze. However, the decrease in aluminum ion content will reduce the hardness and wear resistance of the glaze, reduce the chemical corrosion resistance of the glaze, and lead to poor bonding between the glaze layer and the body, increasing the risk of falling off. Another solution is to increase the content of sodium and potassium ions in the glaze. When the sodium and potassium ion content is high, it can promote the formation of four-coordinated aluminum ions and oxygen ions [AlO4], so that it can be stably present in the glaze grid system. When the sodium and potassium ion content is low, aluminum ions and oxygen ions form six-coordinated [AlO6], which are free outside the grid system, resulting in crystallization and affecting the gloss of the glaze. Therefore, increasing the content of sodium and potassium ions in the glaze is an effective means to solve the problem of aluminum ion crystallization and improve the gloss of the glaze. However, sodium and potassium ions usually exist as fluxes in glazes, which help to reduce the melting temperature of glazes and make glazes easier to apply and shape. However, their high activity also causes these ions to easily diffuse into the ceramic matrix at high temperatures, forming ion exchange. This exchange may not only erode the ceramic matrix and reduce the overall structural strength of the material, but also form microcracks or pores in the glaze layer, thereby reducing the gloss and overall aesthetics of the glaze.

[0004] Therefore, developing a bright hot-bent integrated rock slab basin that can effectively control the crystallization of aluminum ions and limit the excessive diffusion of sodium and potassium ions has become a technical problem that needs to be solved urgently in the industry. In addition, by optimizing the chemical composition of the glaze layer and adopting advanced firing technology, the aesthetics and durability of the product can be further improved to meet the market demand for high-quality ceramic products. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a bright hot-bent integrated rock slab basin and a manufacturing process thereof.

[0006] The present invention provides a bright hot-bent integrated rock slab basin, comprising an embryo layer, a pigment layer and a glaze layer.

[0007] The glaze layer consists of a sodium potassium ion glaze layer and an aluminum ion glaze layer.

[0008] The glaze of the sodium-potassium ion glaze layer is composed of the following raw materials in parts by mass:

[0009] Sodium feldspar: 3-5 parts;

[0010] Potassium feldspar: 5-10 parts;

[0011] Talc: 1-3 parts;

[0012] Quartz: 1-2 parts;

[0013] Barium carbonate: 0.6-1 part;

[0014] Magnesium carbonate: 1.5-3 parts;

[0015] Zinc oxide: 0.1-0.3 parts;

[0016] Sodium silicate: 0.3-0.8 parts;

[0017] Borax: 3-5 parts.

[0018] The glaze of the aluminum ion glaze layer is composed of the following raw materials in parts by mass:

[0019] Kaolin: 5-10 parts;

[0020] Talc: 1-1.4 parts;

[0021] Quartz: 2-2.8 parts;

[0022] Silica: 1-3 parts;

[0023] Sillimanite: 3-5 parts;

[0024] Borax: 0.6-1.2 parts.

[0025] The embryo layer includes the following raw materials by weight:

[0026] Sodium feldspar: 20-30 parts;

[0027] Potassium-sodium feldspar: 15-20 parts;

[0028] Kaolin: 30-35 parts;

[0029] High-strength soil: 3-5 parts;

[0030] Silica: 3-6 parts;

[0031] Talc: 1-3 parts;

[0032] Serpentine: 3-5 parts;

[0033] Pyroxene: 3-5 parts;

[0034] Sillimanite: 3-5 parts;

[0035] Pyrophyllite: 3-5 parts;

[0036] Low melting point glass powder: 5-10 parts;

[0037] Fluorine-containing flux: 2-4 parts.

[0038] The fluorine-containing flux is at least one of sodium fluoroaluminate and potassium fluoroaluminate.

[0039] The present invention also provides a manufacturing process for a bright hot-bent integrated rock plate basin, comprising the following steps:

[0040] (1) According to the raw material formula of the embryo layer, sodium feldspar, potassium sodium feldspar, kaolin, high-strength soil, silica, talc, serpentine, pyroxene, sillimanite, pyrophyllite, low-melting-point glass powder and fluorine-containing flux are weighed and mixed, ball-milled for 3-5 hours, and then dried to control the moisture content below 5%. The raw materials are pressed into 3-5 mm by dry pressing process, and the pressing pressure is controlled at 20-30 MPa to obtain an embryo;

[0041] (2) according to the glaze formula of the sodium-potassium ion glaze layer, sodium feldspar, potassium feldspar, talc, quartz, barium carbonate, magnesium carbonate, zinc oxide, sodium silicate, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the sodium-potassium ion glaze layer; according to the glaze formula of the aluminum ion glaze layer, kaolin, talc, quartz, silica, sillimanite, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the aluminum ion glaze layer;

[0042] (3) performing low-temperature plasma treatment on the embryo body obtained in step (1) to improve the degree of surface activation, spraying a pigment layer and applying a glaze with an aluminum ion glaze layer, and then applying a glaze with a sodium potassium ion glaze layer after drying, and drying again to obtain a preheated curved rock board;

[0043] (4) The preheated bent rock slab obtained in step (3) is heated to 1100-1150°C at a rate of 5-10°C / min, and treated at a constant temperature for 40-280min. Then, it is hot-bent by a mold at 1100-1150°C, and the molding time is controlled at 5-10min. Finally, it is cooled to room temperature at 3-6°C / min to obtain the bright hot-bent integrated rock slab basin.

[0044] The ball milling in step (1) uses 0.5wt%-2wt% γ-aminopropyltriethoxysilane ethanol solution as a ball milling aid.

[0045] The gas used for the low-temperature plasma treatment in step (3) is a mixture of oxygen and argon in a volume ratio of 1: (0.5-1), with a power of 100-300W, a gas pressure of 0.1-0.5Torr, and a time of 5-10min.

[0046] The problem solved by the present invention is that a high content of aluminum ions in ceramic glazes will lead to crystallization, while a low content of aluminum ions will affect the mechanical properties and chemical corrosion resistance of the glaze surface and reduce the adhesion between the glaze surface and the body; while sodium and potassium ions can effectively limit the crystallization problem of aluminum ions, but sodium and potassium ions are easy to diffuse into the ceramic matrix at high temperatures to form ion exchange. This exchange may not only corrode the ceramic matrix and reduce the overall structural strength of the material, but also form microcracks or pores in the glaze layer, thereby reducing the glossiness and overall aesthetics of the glaze surface.

[0047] In order to increase the aluminum ion content in the glaze and reduce the crystallization of aluminum ions and the diffusion of sodium and potassium ions, the present invention adopts a double-layer glazing method, firstly applying a layer of glaze with high aluminum ion content on the blank, and then applying a layer of glaze with high sodium and potassium ion content after it is dried, wherein the aluminum ion content in the glaze is regulated by adding sillimanite, and the sodium and potassium ion content is regulated by adding sodium silicate, and an aluminum ion glaze layer and a sodium and potassium ion glaze layer are respectively obtained, and the aluminum ion glaze layer is used to prevent the sodium and potassium ions from diffusing into the blank. In addition, the sodium and potassium ion layer can also effectively prevent the crystallization of aluminum ions.

[0048] In alkali or alkaline earth silicate glasses, Al2O3 enters the structure in two coordination states: [AlO4] and [AlO6], depending on the composition and amount of the modified oxide. In alkali-containing glasses, Al2O3 is mainly tetrahedral coordinated, while alkaline earth glasses can accommodate additional numbers of pentahedral and octahedral coordinated alumina. The coordination diversity is related to the strength of the cation field. When Al2O3 / R2O<1 (R=Li,Na,K), Al 3+ Enter alarm, [AlO4] is formed; when Al2O3 / R2O>1, Al 3+ Then a hexacoordinate system is formed, and the network external body is located in the octahedron. + and Al 3+ The interface distribution curve shows that at 1473K and 1523K, in the interface transition zone (within 200μm on the right side of the dotted line), the content of Na+ diffusion is high, and the ratio of Na2O to Al2O3 is greater than 1, so Al 3+ It exists in the form of four coordination. As the amount of Na+ diffusion decreases outside the interface transition zone, the ratio of Na2O to Al2O3 content is less than 1, that is, Al3+ It is stored in the octahedron. According to the ion distribution curve Al 3+ and Mg 2+ There are also peaks, both crystal analysis and glass analysis of spinel MgAl2O4. Al in spinel (MgAl2O4) 3+ It exists in the form of octahedron. Therefore, Na + By diffusion equivalent to Al 3+ The coordination of , thereby affecting the analysis of glass crystals.

[0049] When the content of sodium and potassium ions is high, they can promote aluminum ions and oxygen ions to form a tetracoordinate [AlO4], so that they can exist stably in the glaze grid system. When the content of sodium and potassium ions is low, aluminum ions and oxygen ions form a hexacoordinate [AlO6], which is free outside the grid system, resulting in crystallization and affecting the gloss of the glaze. Therefore, increasing the content of sodium and potassium ions in the glaze is an effective means to solve the problem of aluminum ion crystallization and improve the gloss of the glaze. However, sodium and potassium ions usually exist as fluxes in glazes, which helps to reduce the melting temperature of glazes and make glazes easier to apply and form. However, their high activity also causes these ions to easily diffuse into the ceramic matrix at high temperatures, forming ion exchange. This exchange may not only corrode the ceramic matrix and reduce the overall structural strength of the material, but also form microcracks or pores in the glaze layer, thereby reducing the gloss and overall aesthetics of the glaze. The diffusion of sodium and potassium ions is unstoppable, especially in the hot bending process, where higher temperatures are more favorable conditions for their diffusion.

[0050] To address this problem, the present invention adopts a double-layer glazing method, firstly applying a layer of glaze with high aluminum ion content on the blank, and then applying a layer of glaze with high sodium and potassium ion content after it is dried, wherein the aluminum ion content in the glaze is regulated by adding sillimanite, and the sodium and potassium ion content is regulated by adding sodium silicate, thereby obtaining an aluminum ion glaze layer and a sodium and potassium ion glaze layer respectively, and the aluminum ion glaze layer is used to prevent the sodium and potassium ions from diffusing into the blank. In addition, the sodium and potassium ion layer can also effectively prevent the crystallization of aluminum ions, thereby developing a bright hot-bent integrated rock slab basin that can effectively control the crystallization of aluminum ions and limit the excessive diffusion of sodium and potassium ions.

[0051] Beneficial effects of the present invention:

[0052] The present invention adopts a double-layer glazing method, firstly applying a layer of glaze with high aluminum ion content on the blank, and then applying a layer of glaze with high sodium and potassium ion content after it is dried, wherein the aluminum ion content in the glaze is regulated by adding sillimanite, and the sodium and potassium ion content is regulated by adding sodium silicate, thereby obtaining an aluminum ion glaze layer and a sodium and potassium ion glaze layer respectively, and the aluminum ion glaze layer is used to prevent the sodium and potassium ions from diffusing into the blank. In addition, the sodium and potassium ion layer can also effectively prevent the crystallization of aluminum ions, thereby developing a bright hot-bent integrated rock slab basin that can effectively control the crystallization of aluminum ions and limit the excessive diffusion of sodium and potassium ions. DETAILED DESCRIPTION

[0053] Sillimanite: 43.60wt% SiO2, 46.80wt% Al2O3, 0.65wt% Fe2O3, 0.08wt% TiO2, 0.35wt% CaO, 0.10wt% MgO, 1.20wt% K2O, 0.40wt% Na2O, 5.30wt% LOI.

[0054] Kaolin: 50.00wt% SiO2, 35.00wt% Al2O3, 0.64wt% Fe2O3, 0.05wt% TiO2, 0.29wt% CaO, 0.14wt% MgO, 1.57wt% K2O, 0.49wt% Na2O, 11.74wt% LOI.

[0055] High-strength soil: 70.29wt% SiO2, 14.83wt% Al2O3, 0.54wt% Fe2O3, 0.11wt% TiO2, 2.75wt% CaO, 2.36wt% MgO, 0.60wt% K2O, 0.57wt% Na2O, 7.73wt% LOI.

[0056] Low melting point glass powder: No.: 9012, initial melting point: 770, Foshan Taoyise Glaze Co., Ltd.

[0057] Sodium polycarboxylate, product number TB-555815146015, Tianjin Baima Technology Co., Ltd.

[0058] The pigment layer pigment used in the embodiments and comparative examples is cobalt blue pigment, model: SPP-2008, Suzhou David New Material Technology Co., Ltd.

[0059] Example 1

[0060] A bright hot-bent integrated rock slab basin comprises an embryo layer, a pigment layer and a glaze layer.

[0061] The glaze layer consists of a sodium potassium ion glaze layer and an aluminum ion glaze layer.

[0062] The glaze of the sodium-potassium ion glaze layer is composed of the following raw materials in parts by mass:

[0063] Sodium feldspar: 4.2 parts;

[0064] Potassium feldspar: 7.8 parts;

[0065] Talc: 2.3 parts;

[0066] Quartz: 1.6 parts;

[0067] Barium carbonate: 0.8 parts;

[0068] Magnesium carbonate: 2.1 parts;

[0069] Zinc oxide: 0.2 parts;

[0070] Sodium silicate: 0.6 parts;

[0071] Borax: 4 parts.

[0072] The glaze of the aluminum ion glaze layer is composed of the following raw materials in parts by mass:

[0073] Kaolin: 8 parts;

[0074] Talc: 1.2 parts;

[0075] Quartz: 2.3 parts;

[0076] Silica: 1.8 parts;

[0077] Sillimanite: 3.6 parts;

[0078] Borax: 0.9 parts.

[0079] The embryo layer includes the following raw materials by weight:

[0080] Sodium feldspar: 25 parts;

[0081] Potassium-sodium feldspar: 15 parts;

[0082] Kaolin: 35 parts;

[0083] High strength soil: 3 parts;

[0084] Silica: 6 parts;

[0085] Talc: 2 parts;

[0086] Serpentine: 3 parts;

[0087] Pyroxene: 3 parts;

[0088] Sillimanite: 3 parts;

[0089] Pyrophyllite: 5 parts;

[0090] Low melting point glass powder: 7 parts;

[0091] Sodium fluoroaluminate: 3 parts.

[0092] A manufacturing process of a bright hot-bent integrated rock plate basin comprises the following steps:

[0093] (1) According to the raw material formula of the embryo layer, sodium feldspar, potassium sodium feldspar, kaolin, high-strength soil, silica, talc, serpentine, pyroxene, sillimanite, pyrophyllite, low-melting-point glass powder and sodium fluoroaluminate are weighed and mixed, ball-milled for 4 hours, and then dried to control the moisture content below 5%. The raw materials are pressed into 4 mm by dry pressing process, and the pressing pressure is controlled at 25 MPa to obtain an embryo;

[0094] (2) according to the glaze formula of the sodium-potassium ion glaze layer, sodium feldspar, potassium feldspar, talc, quartz, barium carbonate, magnesium carbonate, zinc oxide, sodium silicate, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the sodium-potassium ion glaze layer; according to the glaze formula of the aluminum ion glaze layer, kaolin, talc, quartz, silica, sillimanite, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the aluminum ion glaze layer;

[0095] (3) performing low-temperature plasma treatment on the embryo body obtained in step (1) to improve the degree of surface activation, spraying a pigment layer and applying a glaze with an aluminum ion glaze layer, and then applying a glaze with a sodium potassium ion glaze layer after drying, and drying again to obtain a preheated curved rock board;

[0096] (4) The preheated bent rock slab obtained in step (3) is heated to 1120°C at a rate of 10°C / min, and treated at a constant temperature for 60 minutes. Then, it is hot-bent by a mold at 1120°C, and the molding time is controlled at 6 minutes. Finally, it is cooled to room temperature at a rate of 5°C / min to obtain the bright hot-bent integrated rock slab basin.

[0097] The ball milling in step (1) uses 1.5 wt % γ-aminopropyltriethoxysilane ethanol solution as a ball milling aid.

[0098] The dispersant in step (2) is sodium polycarboxylate, accounting for 3‰ of the total mass; the water accounts for 24% of the total mass.

[0099] The coating weight of the aluminum ion glaze layer and the sodium potassium ion glaze layer applied in step (3) is the same, both of which are 1.0 g / cm 3 .

[0100] The gas used for the low-temperature plasma treatment in step (3) is a mixture of oxygen and argon in a volume ratio of 1:0.8, with a power of 200 W, a gas pressure of 0.3 Torr, and a time of 8 min.

[0101] Example 2

[0102] A bright hot-bent integrated rock slab basin comprises an embryo layer, a pigment layer and a glaze layer.

[0103] The glaze layer consists of a sodium potassium ion glaze layer and an aluminum ion glaze layer.

[0104] The glaze of the sodium-potassium ion glaze layer is composed of the following raw materials in parts by mass:

[0105] Sodium feldspar: 4.2 parts;

[0106] Potassium feldspar: 7.8 parts;

[0107] Talc: 2.3 parts;

[0108] Quartz: 1.6 parts;

[0109] Barium carbonate: 0.8 parts;

[0110] Magnesium carbonate: 2.1 parts;

[0111] Zinc oxide: 0.2 parts;

[0112] Borax: 4 parts.

[0113] The glaze of the aluminum ion glaze layer is composed of the following raw materials in parts by mass:

[0114] Kaolin: 8 parts;

[0115] Talc: 1.2 parts;

[0116] Quartz: 2.3 parts;

[0117] Silica: 1.8 parts;

[0118] Sillimanite: 3.6 parts;

[0119] Borax: 0.9 parts.

[0120] The embryo layer includes the following raw materials by weight:

[0121] Sodium feldspar: 25 parts;

[0122] Potassium-sodium feldspar: 15 parts;

[0123] Kaolin: 35 parts;

[0124] High strength soil: 3 parts;

[0125] Silica: 6 parts;

[0126] Talc: 2 parts;

[0127] Serpentine: 3 parts;

[0128] Pyroxene: 3 parts;

[0129] Sillimanite: 3 parts;

[0130] Pyrophyllite: 5 parts;

[0131] Low melting point glass powder: 7 parts;

[0132] Sodium fluoroaluminate: 3 parts.

[0133] A manufacturing process of a bright hot-bent integrated rock plate basin comprises the following steps:

[0134] (1) According to the raw material formula of the embryo layer, sodium feldspar, potassium sodium feldspar, kaolin, high-strength soil, silica, talc, serpentine, pyroxene, sillimanite, pyrophyllite, low-melting-point glass powder and sodium fluoroaluminate are weighed and mixed, ball-milled for 4 hours, and then dried to control the moisture content below 5%. The raw materials are pressed into 4 mm by dry pressing process, and the pressing pressure is controlled at 25 MPa to obtain an embryo;

[0135] (2) according to the glaze formula of the sodium-potassium ion glaze layer, sodium feldspar, potassium feldspar, talc, quartz, barium carbonate, magnesium carbonate, zinc oxide, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the sodium-potassium ion glaze layer; according to the glaze formula of the aluminum ion glaze layer, kaolin, talc, quartz, silica, sillimanite, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the aluminum ion glaze layer;

[0136] (3) performing low-temperature plasma treatment on the embryo body obtained in step (1) to improve the degree of surface activation, spraying a pigment layer and applying a glaze with an aluminum ion glaze layer, and then applying a glaze with a sodium potassium ion glaze layer after drying, and drying again to obtain a preheated curved rock board;

[0137] (4) The preheated bent rock slab obtained in step (3) is heated to 1120°C at a rate of 10°C / min, and treated at a constant temperature for 60 minutes. Then, it is hot-bent by a mold at 1120°C, and the molding time is controlled at 6 minutes. Finally, it is cooled to room temperature at a rate of 5°C / min to obtain the bright hot-bent integrated rock slab basin.

[0138] The ball milling in step (1) uses 1.5 wt % γ-aminopropyltriethoxysilane ethanol solution as a ball milling aid.

[0139] The dispersant in step (2) is sodium polycarboxylate, accounting for 3‰ of the total mass; the water accounts for 24% of the total mass.

[0140] The coating weight of the aluminum ion glaze layer and the sodium potassium ion glaze layer applied in step (3) is the same, both of which are 1.0 g / cm 3 .

[0141] The gas used for the low-temperature plasma treatment in step (3) is a mixture of oxygen and argon in a volume ratio of 1:0.8, with a power of 200 W, a gas pressure of 0.3 Torr, and a time of 8 min.

[0142] Example 3

[0143] A bright hot-bent integrated rock slab basin comprises an embryo layer, a pigment layer and a glaze layer.

[0144] The glaze layer consists of a sodium potassium ion glaze layer and an aluminum ion glaze layer.

[0145] The glaze of the sodium-potassium ion glaze layer is composed of the following raw materials in parts by mass:

[0146] Sodium feldspar: 4.2 parts;

[0147] Potassium feldspar: 7.8 parts;

[0148] Talc: 2.3 parts;

[0149] Quartz: 1.6 parts;

[0150] Barium carbonate: 0.8 parts;

[0151] Magnesium carbonate: 2.1 parts;

[0152] Zinc oxide: 0.2 parts;

[0153] Sodium silicate: 0.6 parts;

[0154] Borax: 4 parts.

[0155] The glaze of the aluminum ion glaze layer is composed of the following raw materials in parts by mass:

[0156] Kaolin: 8 parts;

[0157] Talc: 1.2 parts;

[0158] Quartz: 2.3 parts;

[0159] Silica: 1.8 parts;

[0160] Borax: 0.9 parts.

[0161] The embryo layer includes the following raw materials by weight:

[0162] Sodium feldspar: 25 parts;

[0163] Potassium-sodium feldspar: 15 parts;

[0164] Kaolin: 35 parts;

[0165] High strength soil: 3 parts;

[0166] Silica: 6 parts;

[0167] Talc: 2 parts;

[0168] Serpentine: 3 parts;

[0169] Pyroxene: 3 parts;

[0170] Sillimanite: 3 parts;

[0171] Pyrophyllite: 5 parts;

[0172] Low melting point glass powder: 7 parts;

[0173] Sodium fluoroaluminate: 3 parts.

[0174] A manufacturing process of a bright hot-bent integrated rock plate basin comprises the following steps:

[0175] (1) According to the raw material formula of the embryo layer, sodium feldspar, potassium sodium feldspar, kaolin, high-strength soil, silica, talc, serpentine, pyroxene, sillimanite, pyrophyllite, low-melting-point glass powder and sodium fluoroaluminate are weighed and mixed, ball-milled for 4 hours, and then dried to control the moisture content below 5%. The raw materials are pressed into 4 mm by dry pressing process, and the pressing pressure is controlled at 25 MPa to obtain an embryo;

[0176] (2) according to the glaze formula of the sodium-potassium ion glaze layer, sodium feldspar, potassium feldspar, talc, quartz, barium carbonate, magnesium carbonate, zinc oxide, sodium silicate, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the sodium-potassium ion glaze layer; according to the glaze formula of the aluminum ion glaze layer, kaolin, talc, quartz, silica, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the aluminum ion glaze layer;

[0177] (3) performing low-temperature plasma treatment on the embryo body obtained in step (1) to improve the degree of surface activation, spraying a pigment layer and applying a glaze with an aluminum ion glaze layer, and then applying a glaze with a sodium potassium ion glaze layer after drying, and drying again to obtain a preheated curved rock board;

[0178] (4) The preheated bent rock slab obtained in step (3) is heated to 1120°C at a rate of 10°C / min, and treated at a constant temperature for 60 minutes. Then, it is hot-bent by a mold at 1120°C, and the molding time is controlled at 6 minutes. Finally, it is cooled to room temperature at a rate of 5°C / min to obtain the bright hot-bent integrated rock slab basin.

[0179] The ball milling in step (1) uses 1.5 wt % γ-aminopropyltriethoxysilane ethanol solution as a ball milling aid.

[0180] The dispersant in step (2) is sodium polycarboxylate, accounting for 3‰ of the total mass; the water accounts for 24% of the total mass.

[0181] The coating weight of the aluminum ion glaze layer and the sodium potassium ion glaze layer applied in step (3) is the same, both of which are 1.0 g / cm 3 .

[0182] The gas used for the low-temperature plasma treatment in step (3) is a mixture of oxygen and argon in a volume ratio of 1:0.8, with a power of 200 W, a gas pressure of 0.3 Torr, and a time of 8 min.

[0183] Comparative Example 1

[0184] A bright hot-bent integrated rock slab basin comprises an embryo layer, a pigment layer and a glaze layer.

[0185] The glaze layer consists of a sodium potassium ion glaze layer and an aluminum ion glaze layer.

[0186] The glaze of the sodium-potassium ion glaze layer is composed of the following raw materials in parts by mass:

[0187] Sodium feldspar: 4.2 parts;

[0188] Potassium feldspar: 7.8 parts;

[0189] Talc: 2.3 parts;

[0190] Quartz: 1.6 parts;

[0191] Barium carbonate: 0.8 parts;

[0192] Magnesium carbonate: 2.1 parts;

[0193] Zinc oxide: 0.2 parts;

[0194] Sodium silicate: 0.6 parts;

[0195] Borax: 4 parts.

[0196] The glaze of the aluminum ion glaze layer is composed of the following raw materials in parts by mass:

[0197] Kaolin: 8 parts;

[0198] Talc: 1.2 parts;

[0199] Quartz: 2.3 parts;

[0200] Silica: 1.8 parts;

[0201] Sillimanite: 3.6 parts;

[0202] Borax: 0.9 parts.

[0203] The embryo layer includes the following raw materials by weight:

[0204] Sodium feldspar: 25 parts;

[0205] Potassium-sodium feldspar: 15 parts;

[0206] Kaolin: 35 parts;

[0207] High strength soil: 3 parts;

[0208] Silica: 6 parts;

[0209] Talc: 2 parts;

[0210] Serpentine: 3 parts;

[0211] Pyroxene: 3 parts;

[0212] Sillimanite: 3 parts;

[0213] Pyrophyllite: 5 parts;

[0214] Low melting point glass powder: 7 parts;

[0215] Sodium fluoroaluminate: 3 parts.

[0216] A manufacturing process of a bright hot-bent integrated rock plate basin comprises the following steps:

[0217] (1) According to the raw material formula of the embryo layer, sodium feldspar, potassium sodium feldspar, kaolin, high-strength soil, silica, talc, serpentine, pyroxene, sillimanite, pyrophyllite, low-melting-point glass powder and sodium fluoroaluminate are weighed and mixed, ball-milled for 4 hours, and then dried to control the moisture content below 5%. The raw materials are pressed into 4 mm by dry pressing process, and the pressing pressure is controlled at 25 MPa to obtain an embryo;

[0218] (2) according to the glaze formula of the sodium-potassium ion glaze layer, sodium feldspar, potassium feldspar, talc, quartz, barium carbonate, magnesium carbonate, zinc oxide, sodium silicate, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the sodium-potassium ion glaze layer; according to the glaze formula of the aluminum ion glaze layer, kaolin, talc, quartz, silica, sillimanite, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the aluminum ion glaze layer;

[0219] (3) performing low-temperature plasma treatment on the embryo body obtained in step (1) to improve the degree of surface activation, spraying a pigment layer and applying a glaze with a sodium-potassium ion glaze layer, and then applying a glaze with an aluminum ion glaze layer after drying, and drying again to obtain a preheated curved rock board;

[0220] (4) The preheated bent rock slab obtained in step (3) is heated to 1120°C at a rate of 10°C / min, and treated at a constant temperature for 60 minutes. Then, it is hot-bent by a mold at 1120°C, and the molding time is controlled at 6 minutes. Finally, it is cooled to room temperature at a rate of 5°C / min to obtain the bright hot-bent integrated rock slab basin.

[0221] The ball milling in step (1) uses 1.5 wt % γ-aminopropyltriethoxysilane ethanol solution as a ball milling aid.

[0222] The dispersant in step (2) is sodium polycarboxylate, accounting for 3‰ of the total mass; the water accounts for 24% of the total mass.

[0223] The coating weight of the aluminum ion glaze layer and the sodium potassium ion glaze layer applied in step (3) is the same, both of which are 1.0 g / cm 3 .

[0224] The gas used for the low-temperature plasma treatment in step (3) is a mixture of oxygen and argon in a volume ratio of 1:0.8, with a power of 200 W, a gas pressure of 0.3 Torr, and a time of 8 min.

[0225] Comparative Example 2

[0226] A bright hot-bent integrated rock slab basin comprises an embryo layer, a pigment layer and a glaze layer.

[0227] The glaze layer is an aluminum ion glaze layer.

[0228] The glaze of the aluminum ion glaze layer is composed of the following raw materials in parts by mass:

[0229] Kaolin: 8 parts;

[0230] Talc: 1.2 parts;

[0231] Quartz: 2.3 parts;

[0232] Silica: 1.8 parts;

[0233] Sillimanite: 3.6 parts;

[0234] Borax: 0.9 parts.

[0235] The embryo layer includes the following raw materials by weight:

[0236] Sodium feldspar: 25 parts;

[0237] Potassium-sodium feldspar: 15 parts;

[0238] Kaolin: 35 parts;

[0239] High strength soil: 3 parts;

[0240] Silica: 6 parts;

[0241] Talc: 2 parts;

[0242] Serpentine: 3 parts;

[0243] Pyroxene: 3 parts;

[0244] Sillimanite: 3 parts;

[0245] Pyrophyllite: 5 parts;

[0246] Low melting point glass powder: 7 parts;

[0247] Sodium fluoroaluminate: 3 parts.

[0248] A manufacturing process of a bright hot-bent integrated rock plate basin comprises the following steps:

[0249] (1) According to the raw material formula of the embryo layer, sodium feldspar, potassium sodium feldspar, kaolin, high-strength soil, silica, talc, serpentine, pyroxene, sillimanite, pyrophyllite, low-melting-point glass powder and sodium fluoroaluminate are weighed and mixed, ball-milled for 4 hours, and then dried to control the moisture content below 5%. The raw materials are pressed into 4 mm by dry pressing process, and the pressing pressure is controlled at 25 MPa to obtain an embryo;

[0250] (2) according to the glaze formula of the aluminum ion glaze layer, kaolin, talc, quartz, silica, sillimanite, and borax are weighed and mixed, and a dispersant and water are added for grinding to obtain a glaze for the aluminum ion glaze layer;

[0251] (3) performing low-temperature plasma treatment on the embryo body obtained in step (1) to improve the degree of surface activation, spraying a pigment layer and applying a glaze with an aluminum ion glaze layer, and drying to obtain a preheated curved rock board;

[0252] (4) The preheated bent rock slab obtained in step (3) is heated to 1120°C at a rate of 10°C / min, and treated at a constant temperature for 60 minutes. Then, it is hot-bent by a mold at 1120°C, and the molding time is controlled at 6 minutes. Finally, it is cooled to room temperature at a rate of 5°C / min to obtain the bright hot-bent integrated rock slab basin.

[0253] The ball milling in step (1) uses 1.5 wt % γ-aminopropyltriethoxysilane ethanol solution as a ball milling aid.

[0254] The dispersant in step (2) is sodium polycarboxylate, accounting for 3‰ of the total mass; the water accounts for 24% of the total mass.

[0255] The coating weight of the aluminum ion glaze layer applied in step (3) is 2.0 g / cm 3 .

[0256] The gas used for the low-temperature plasma treatment in step (3) is a mixture of oxygen and argon in a volume ratio of 1:0.8, with a power of 200 W, a gas pressure of 0.3 Torr, and a time of 8 min.

[0257] Comparative Example 3

[0258] A bright hot-bent integrated rock slab basin comprises an embryo layer, a pigment layer and a glaze layer.

[0259] The glaze layer is a sodium-potassium ion glaze layer.

[0260] The glaze of the sodium-potassium ion glaze layer is composed of the following raw materials in parts by mass:

[0261] Sodium feldspar: 4.2 parts;

[0262] Potassium feldspar: 7.8 parts;

[0263] Talc: 2.3 parts;

[0264] Quartz: 1.6 parts;

[0265] Barium carbonate: 0.8 parts;

[0266] Magnesium carbonate: 2.1 parts;

[0267] Zinc oxide: 0.2 parts;

[0268] Sodium silicate: 0.6 parts;

[0269] Borax: 4 parts.

[0270] The embryo layer includes the following raw materials by weight:

[0271] Sodium feldspar: 25 parts;

[0272] Potassium-sodium feldspar: 15 parts;

[0273] Kaolin: 35 parts;

[0274] High strength soil: 3 parts;

[0275] Silica: 6 parts;

[0276] Talc: 2 parts;

[0277] Serpentine: 3 parts;

[0278] Pyroxene: 3 parts;

[0279] Sillimanite: 3 parts;

[0280] Pyrophyllite: 5 parts;

[0281] Low melting point glass powder: 7 parts;

[0282] Sodium fluoroaluminate: 3 parts.

[0283] A manufacturing process of a bright hot-bent integrated rock plate basin comprises the following steps:

[0284] (1) According to the raw material formula of the embryo layer, sodium feldspar, potassium sodium feldspar, kaolin, high-strength soil, silica, talc, serpentine, pyroxene, sillimanite, pyrophyllite, low-melting-point glass powder and sodium fluoroaluminate are weighed and mixed, ball-milled for 4 hours, and then dried to control the moisture content below 5%. The raw materials are pressed into 4 mm by dry pressing process, and the pressing pressure is controlled at 25 MPa to obtain an embryo;

[0285] (2) weighing albite, potassium feldspar, talc, quartz, barium carbonate, magnesium carbonate, zinc oxide, sodium silicate, and borax according to the glaze formula of the sodium-potassium ion glaze layer, mixing, adding a dispersant and water for grinding, and obtaining a glaze for the sodium-potassium ion glaze layer;

[0286] (3) performing low-temperature plasma treatment on the embryo body obtained in step (1) to improve the degree of surface activation, spraying a pigment layer and applying a glaze with a sodium-potassium ion glaze layer, and drying to obtain a preheated curved rock board;

[0287] (4) The preheated bent rock slab obtained in step (3) is heated to 1120°C at a rate of 10°C / min, and treated at a constant temperature for 60 minutes. Then, it is hot-bent by a mold at 1120°C, and the molding time is controlled at 6 minutes. Finally, it is cooled to room temperature at a rate of 5°C / min to obtain the bright hot-bent integrated rock slab basin.

[0288] The ball milling in step (1) uses 1.5 wt % γ-aminopropyltriethoxysilane ethanol solution as a ball milling aid.

[0289] The dispersant in step (2) is sodium polycarboxylate, accounting for 3‰ of the total mass; the water accounts for 24% of the total mass.

[0290] The coating weight of the sodium-potassium ion glaze layer applied in step (3) is 2.0 g / cm 3 .

[0291] The gas used for the low-temperature plasma treatment in step (3) is a mixture of oxygen and argon in a volume ratio of 1:0.8, with a power of 200 W, a gas pressure of 0.3 Torr, and a time of 8 min.

[0292] Comparative Example 4

[0293] A bright hot-bent integrated rock slab basin comprises an embryo layer, a pigment layer and a glaze layer.

[0294] The glaze material of the glaze layer is composed of the following raw materials in parts by mass:

[0295] Sodium feldspar: 4.2 parts;

[0296] Potassium feldspar: 7.8 parts;

[0297] Talc: 3.5 parts;

[0298] Quartz: 3.9 parts;

[0299] Barium carbonate: 0.8 parts;

[0300] Magnesium carbonate: 2.1 parts;

[0301] Zinc oxide: 0.2 parts;

[0302] Sodium silicate: 0.6 parts;

[0303] Borax: 4.9 parts;

[0304] Kaolin: 8 parts;

[0305] Silica: 1.8 parts;

[0306] Sillimanite: 3.6 parts.

[0307] The embryo layer includes the following raw materials by weight:

[0308] Sodium feldspar: 25 parts;

[0309] Potassium-sodium feldspar: 15 parts;

[0310] Kaolin: 35 parts;

[0311] High strength soil: 3 parts;

[0312] Silica: 6 parts;

[0313] Talc: 2 parts;

[0314] Serpentine: 3 parts;

[0315] Pyroxene: 3 parts;

[0316] Sillimanite: 3 parts;

[0317] Pyrophyllite: 5 parts;

[0318] Low melting point glass powder: 7 parts;

[0319] Sodium fluoroaluminate: 3 parts.

[0320] A manufacturing process of a bright hot-bent integrated rock plate basin comprises the following steps:

[0321] (1) According to the raw material formula of the embryo layer, sodium feldspar, potassium sodium feldspar, kaolin, high-strength soil, silica, talc, serpentine, pyroxene, sillimanite, pyrophyllite, low-melting-point glass powder and sodium fluoroaluminate are weighed and mixed, ball-milled for 4 hours, and then dried to control the moisture content below 5%. The raw materials are pressed into 4 mm by dry pressing process, and the pressing pressure is controlled at 25 MPa to obtain an embryo;

[0322] (2) weighing albite, potassium feldspar, talc, quartz, barium carbonate, magnesium carbonate, zinc oxide, sodium silicate, borax, kaolin, silica, and sillimanite according to the glaze formula of the glaze layer, mixing, adding a dispersant and water, grinding, and obtaining a glaze;

[0323] (3) performing low-temperature plasma treatment on the embryo body obtained in step (1) to improve the degree of surface activation, spraying a pigment layer and applying a glaze, and drying to obtain a preheated curved rock board;

[0324] (4) The preheated bent rock slab obtained in step (3) is heated to 1120°C at a rate of 10°C / min, and treated at a constant temperature for 60 minutes. Then, it is hot-bent by a mold at 1120°C, and the molding time is controlled at 6 minutes. Finally, it is cooled to room temperature at a rate of 5°C / min to obtain the bright hot-bent integrated rock slab basin.

[0325] The ball milling in step (1) uses 1.5 wt % γ-aminopropyltriethoxysilane ethanol solution as a ball milling aid.

[0326] The dispersant in step (2) is sodium polycarboxylate, accounting for 3‰ of the total mass; the water accounts for 24% of the total mass.

[0327] The coating amount of the glaze applied in step (3) is 2.0 g / cm 3 .

[0328] The gas used for the low-temperature plasma treatment in step (3) is a mixture of oxygen and argon in a volume ratio of 1:0.8, with a power of 200 W, a gas pressure of 0.3 Torr, and a time of 8 min.

[0329] Test Example 1:

[0330] The gloss changes of the bright heat-bent integrated basins of the embodiments and comparative examples after heat bending are shown in Table 1.

[0331] Table 1: Gloss statistics

[0332] Gloss after hot bending / ° Example 1 90-94 Example 2 80-83 Example 3 85-90 Comparative Example 1 80-84 Comparative Example 2 70-75 Comparative Example 3 75-80 Comparative Example 4 82-85

[0333] Test Example 2

[0334] Hardness test, sample size: 2mm×4mm×20mm, fine grinding and polishing of the glaze to ensure smooth surface without scratches. Vickers microhardness tester was used to test the hardness of the sample, with a load of 100gf (100gf=0.98N) and a holding time of 15s. The hardness of the sample was tested at a temperature of 22°C and a relative humidity of 50%. Each sample was measured 10 times and the average value was taken. The results are shown in Table 2.

[0335] Table 2: Hardness test results

[0336] Hardness / GPa Example 1 6.14 Example 2 6.32 Example 3 6.04

[0337] It can be seen from Test Examples 1 and 2 that the present invention adopts a method of first applying a layer of aluminum ion glaze layer on the embryo layer and then applying a layer of sodium potassium ion glaze layer. The final hot-bent integrated rock slab basin has the best gloss and the glossiness decreases the least compared to before hot bending. Example 2 did not add an appropriate amount of sodium silicate to the sodium-potassium ion layer glaze, and Example 3 did not add sillimanite to the aluminum ion glaze layer. The glossiness of the glaze surface was lower than that of Example 1, and the glossiness decreased significantly after hot bending. This shows that the present invention adopts a double-layer glazing method, firstly applying a layer of glaze with a high aluminum ion content on the body, and then applying a layer of glaze with a high sodium-potassium ion content after it is dried, wherein the aluminum ion content in the glaze is regulated by the addition of sillimanite, and the sodium-potassium ion content is regulated by the addition of sodium silicate, thereby obtaining an aluminum ion glaze layer and a sodium-potassium ion glaze layer respectively, and the aluminum ion glaze layer is used to prevent sodium and potassium ions from diffusing into the body, and the sodium-potassium ion layer can also prevent the crystallization of aluminum ions, thereby developing a bright hot-bent integrated rock slab basin that can effectively control the crystallization of aluminum ions and limit the excessive diffusion of sodium and potassium ions. In comparative example 1, a sodium-potassium ion glaze layer is first applied, and then an aluminum-ion glaze layer is applied. In comparative example 4, a sodium-potassium ion layer glaze and an aluminum-ion layer glaze are mixed and applied, and the glossiness thereof is also greatly reduced, which also proves that the crystallization of aluminum ions to the glaze surface and the diffusion of sodium-potassium ions will affect its glossiness. Therefore, a layer of glaze with a high aluminum ion content is first applied to the blank, and after it is dried, a layer of glaze with a high sodium-potassium ion content is applied, wherein the aluminum ion content in the glaze is regulated by the addition of sillimanite, and the sodium-potassium ion content is regulated by the addition of sodium silicate, and an aluminum ion glaze layer and a sodium-potassium ion glaze layer are obtained respectively. The aluminum ion glaze layer is used to prevent the diffusion of sodium-potassium ions to the blank, and the sodium-potassium ion layer can also prevent the crystallization of aluminum ions. This is the most reasonable and effective way to obtain a bright hot-bent integrated rock plate basin with high gloss.

Claims

1. A bright hot-bent integrated rock plate basin, characterized in that: It comprises an embryo layer, a pigment layer and a glaze layer; the glaze layer is composed of a sodium-potassium ion glaze layer and an aluminum-ion glaze layer; the aluminum-ion glaze layer is coated on the surface of the pigment layer, and the sodium-potassium ion glaze layer is coated on the surface of the aluminum-ion glaze layer; The glaze of the sodium-potassium ion glaze layer is composed of the following raw materials in parts by mass: Sodium feldspar: 3-5 parts; Potassium feldspar: 5-10 parts; Talc: 1-3 parts; Quartz: 1-2 parts; Barium carbonate: 0.6-1 part; Magnesium carbonate: 1.5-3 parts; Zinc oxide: 0.1-0.3 parts; Sodium silicate: 0.3-0.8 parts; Borax: 3-5 parts; The glaze of the aluminum ion glaze layer is composed of the following raw materials in parts by mass: Kaolin: 5-10 parts; Talc: 1-1.4 parts; Quartz: 2-2.8 parts; Silica: 1-3 parts; Sillimanite: 3-5 parts; Borax: 0.6-1.2 parts.

2. The bright hot-bent integrated rock slab basin as claimed in claim 1, characterized in that: The embryo layer includes the following raw materials by weight: Sodium feldspar: 20-30 parts; Potassium-sodium feldspar: 15-20 parts; Kaolin: 30-35 parts; High-strength soil: 3-5 parts; Silica: 3-6 parts; Talc: 1-3 parts; Serpentine: 3-5 parts; Pyroxene: 3-5 parts; Sillimanite: 3-5 parts; Pyrophyllite: 3-5 parts; Low melting point glass powder: 5-10 parts; Fluorine-containing flux: 2-4 parts.

3. The bright hot-bent integrated rock slab basin as claimed in claim 2, characterized in that: The fluorine-containing flux is at least one of sodium fluoroaluminate and potassium fluoroaluminate.

4. A manufacturing process for a bright hot-bent integrated rock slab basin as claimed in any one of claims 1 to 3, characterized in that: The steps include: (1) According to the raw material formula of the embryo layer, sodium feldspar, potassium sodium feldspar, kaolin, high-strength clay, silica, talc, serpentine, pyroxene, sillimanite, pyrophyllite, low-melting-point glass powder and fluorine-containing flux are weighed and mixed, ball-milled for 3-5 hours, and then dried to control the moisture content below 5%. The raw materials are pressed into 3-5 mm by dry pressing process, and the pressing pressure is controlled at 20-30 MPa to obtain the embryo; (2) According to the glaze formula of the sodium-potassium ion glaze layer, sodium feldspar, potassium feldspar, talc, quartz, barium carbonate, magnesium carbonate, zinc oxide, sodium silicate, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the sodium-potassium ion glaze layer; according to the glaze formula of the aluminum ion glaze layer, kaolin, talc, quartz, silica, sillimanite, and borax are weighed, mixed, and a dispersant and water are added for grinding to obtain a glaze for the aluminum ion glaze layer; (3) performing low-temperature plasma treatment on the embryo body obtained in step (1) to improve the degree of surface activation, spraying a pigment layer and applying a glaze with an aluminum ion glaze layer, and then applying a glaze with a sodium potassium ion glaze layer after drying, and then drying again to obtain a preheated curved rock board; (4) The preheated bent rock plate obtained in step (3) is heated to 1100-1150°C at a rate of 5-10°C / min, and treated at a constant temperature for 40-280min. Then, it is hot-bent by a mold at 1100-1150°C, and the molding time is controlled at 5-10min. Finally, it is cooled to room temperature at 3-6°C / min to obtain the bright hot-bent integrated rock plate basin.

5. The manufacturing process of the bright hot-bent integrated rock slab basin as claimed in claim 4, characterized in that: In step (1), the ball milling uses 0.5wt%-2wt% γ-aminopropyltriethoxysilane ethanol solution as a ball milling aid.

6. The manufacturing process of the bright hot-bent integrated rock slab basin as claimed in claim 4, characterized in that: The gas used for the low-temperature plasma treatment in step (3) is a mixture of oxygen and argon in a volume ratio of 1: (0.5-1), with a power of 100-300 W, a gas pressure of 0.1-0.5 Torr, and a time of 5-10 min.

Citation Information

Patent Citations

  • High-curvature wide-color-gamut ceramic curved surface rock plate and preparation method and application thereof

    CN113979738A

  • Wear-resistant color-assisting frit for wear-resistant glaze, super wear-resistant glaze and ceramic tile preparation method

    CN114573233A